Low-density lipoprotein-cholesterol lowering effect of a nutraceutical regimen with or without ezetimibe in hypercholesterolaemic patients with statin intolerance - Ward, Natalie C.; Reid, Christopher M.; Watts, Gerald F. (Frontiers in Cardiovascular Medicine, 2022)
Background Statins are the most widely prescribed medication to lower low-density lipoprotein cholesterol (LDL-c). However, a significant portion of patients are unable to tolerate them due to side effects, most commonly muscle related. Nutraceuticals, natural plant derivatives with lipid-lowering properties, may provide an alternative to lower LDL-c in these patients. Aims To investigate whether a nutraceutical regimen, either alone or in combination with ezetimibe, can lower LDL-c in patients with hypercholesterolemia who are intolerant to statins. Methods Participants were recruited into a double-blind, randomized, placebo-controlled intervention study. Treatments were (i) placebo, (ii) nutraceutical (500 mg berberine, 200 mg red yeast rice (RYR), 2 g plant sterols)/daily, (iii) ezetimibe (10 mg)/daily, or (iv) the combination of nutraceutical and ezetimibe/daily. At baseline and week 8, all participants provide a fasting blood sample for assessment of lipid profile and safety bloods. Results Fifty participants were randomized, with 44 completing the treatment period. Following adjustment for baseline levels and compared with placebo, LDL-c was significantly reduced (all p < 0.0001) with ezetimibe (−1.02 mmol/L), nutraceutical (−1.15 mmol/L) and the nutraceutical and ezetimibe combination (−1.92 mmol/L). Non-HDL cholesterol was significantly reduced (all p < 0.0001) with ezetimibe (−1.29 mmol/L), nutraceutical (−1.37 mmol/L) and the nutraceutical and ezetimibe combination (−2.18 mmol/L). Remnant cholesterol and triglycerides was significantly reduced with the nutraceutical and ezetimibe combination (p = 0.018). Conclusion A nutraceutical regimen (berberine, RYR and plant sterols) and ezetimibe independently and additively lower LDL-c in patients with hypercholesterolemia who are intolerant to statins.